Alston family papers - Alston, Jacob Motte, 1821-1909.; Alston, Mary Motte; Alston, Theodosia Burr, 1783-1813.
Land grants, plats, deeds, legal papers, pew rent records, family history, genealogical notes, transcripts of Bible records, scrapbooks, account book, reminiscences, and printed material of Jacob Motte Alston, his daughter, Mary Motte Alston, and Theodosia Burr Alston. Relates to Southern history and politics.
Alston or Allston family members including Jacob Motte Alston, his daughter, Mary Motte Alston, and Theodosia Burr Alston, daughter of Aaron Burr and wife of Joseph Alston (1778-1816).
Collection material in English.
Keywords: Alston, Joseph, -- 1778-1816 -- Family; Burr, Aaron, -- 1756-1836 -- Family; Alston family; Deeds -- Southern States; Land grants -- Southern States; Southern States -- History; Southern States -- Politics and government